Evaluation of irradiation and Termin-8® addition to spray-dried animal plasma, base mix and/or whole diet on growth performance of nursery pigs - R E Musser; W N Cannon; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
Two studies were conducted to evaluate the effects of irradiation of spray-dried animal plasma and Termin-8ï›š treatment to spray-dried animal plasma, base mix (specialty protein products, milk products, ground oat groats, soy flour, flow agent, vitamins, and minerals), or whole diet on nursery pig performance. Overall (d 0 to 14) in Exp. 1, pigs fed diets containing irradiated plasma had increased ADG and pigs fed Termin-8Â® treated plasma had increased ADG and ADFI compared to pigs fed diets with regular plasma or whole diets (containing either regular or irradiated plasma) treated with Termin-8. No differences in F/G were observed among treatments. In Exp. 2, pigs fed diets that contained either animal plasma or base mix treated with Termin-8 in the SEW diet had increased ADG and F/G from d 0 to 13 compared to no Termin-8 treatment, but no differences were observed overall (d 0 to 40). Therefore, the use of irradiated spray-dried animal plasma and Termin-8 treated spray-dried animal plasma and base mix improves growth performance in nursery pigs during the initial period after weaning.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Irradiation; Termin-8Â®; Nursery pig